2017
DOI: 10.1007/s11060-017-2445-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathological analysis of the surgical margins of resected glioblastomas excised using photodynamic visualization with both 5-aminolevulinic acid and fluorescein sodium

Abstract: During glioma resection, 5-aminolevulinic acid (5-ALA) and fluorescein sodium (Fl-Na) are used for photodynamic tumor visualization. The objective of this study was to evaluate the pathological findings of the boundary zone between the tumor and adjacent normal brain in glioblastoma patients undergoing simultaneous double staining with 5-ALA and Fl-Na during surgery. Eight patients received 5-ALA (20 mg/kg orally) before the induction of general anesthesia, and Fl-Na (20 mg/kg) was administered intravenously b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 30 publications
(32 reference statements)
0
21
0
Order By: Relevance
“…Cavity margins after 5-ALA assisted resection even when clear of any fluorescence on surgical microscope examination tend to have isolated GB nests or single cells on microscopy, some of which fluoresce weakly, some of which do not fluoresce [20,21,22,23,24].…”
Section: Intraoperative Fluorescence Tumor Demarcationmentioning
confidence: 99%
“…Cavity margins after 5-ALA assisted resection even when clear of any fluorescence on surgical microscope examination tend to have isolated GB nests or single cells on microscopy, some of which fluoresce weakly, some of which do not fluoresce [20,21,22,23,24].…”
Section: Intraoperative Fluorescence Tumor Demarcationmentioning
confidence: 99%
“…First, and perhaps the most critical step, is to establish a biological context and understanding of the pattern of sub-cellular PpIX expression that is visualized with an optical-sectioning microscope. Note that numerous studies have already shown that PpIX expression provides specific delineation of a variety of neoplasms under wide-field (low-resolution) imaging and spectroscopy (52, 74, 75), including a general correlation between PpIX concentrations and proliferative score as well as World Health Organization (WHO) histologic score (52). Preliminary studies [e.g., using high-resolution in vivo microscopy (55), or using fluorescent-activated cell sorting of dissociated human cells [unpublished data]] have also shown that PpIX expression at the cellular level is highly tumor-specific.…”
Section: Challenges and Future Stepsmentioning
confidence: 99%
“…5-ALA may be even more special than PET because it does not consider only the general quantitative aspect of metabolism and goes beyond. Its mechanism relates to a metabolic phenomenon of a pathway typical from a tumor tissue and not from a normal tissue [34].…”
Section: -Aminolevulinic Acidmentioning
confidence: 99%